IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH ROLE PLAY AND PICTURE AND PICTURE AT SMP NEGERI 1 RATAHAN - Tini Mogea (Jurnal Pendidikan dan Sastra Inggris, 2023)
The purpose of this research is to prove whether role play and picture-in-picture are effective or not in improving students’ speaking abilities at SMP Negeri 1 Ratahan. This research is classified as "classroom action research" because it was conducted in a cycle. The second-grade students were taken as a sample consisting of 20 students. The writer used a reflective journal, field notes, and tests in collecting data. The data were analyzed in a way that triangulates the data sources. It compared the data obtained from reflexive journals, field notes, and tests. This was intended to get a general description of the students' progress. The triangulation was interpreted to get the result of the research. The findings of this study revealed that by using role play in Cycle 1, only a small number of students improved their speaking competency, with a mean score of 5. By applying picture and picture in Cycle 2, more students were able to speak, with a mean score of 6. The result was classified as moderate. Through the combination of role play and picture-and-picture in Cycle 3, most of the students made great progress, with a mean score of 8, and it was categorized as good.